2018
DOI: 10.1029/2018jd028381
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Top Phase Distributions of Simulated Deep Convective Clouds

Abstract: Space‐based observations of the thermodynamic cloud phase are frequently used for the analysis of aerosol indirect effects and other regional and temporal trends of cloud properties; yet they are mostly limited to the cloud top layers. This study addresses the information content in cloud top phase distributions of deep convective clouds during their growing stage. A cloud‐resolving model with grid spacings of 300 m and lower is used in two different setups, simulating idealized and semiidealized isolated conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…They found T g between −15 • C and −38 • C, which is in agreement with values retrieved in Table 1. It is not straightforward to compare passive satellite measurements with models: Hoose et al (2018) showed that some processes such as rime splittering at −10 • C are not detectable by passive satellites due to spatial resolution coarser than 1 km. Also, the cloud top phase transition temperature is more likely to be shifted to higher temperatures than in cloud due to a stronger Wegner-Bergeron-Findeisen process at cloud top (Hoose et al, 2018;Korolev et al, 2017).…”
Section: Larger Cth Have Been Observed Associated With Larger Rmentioning
confidence: 99%
See 1 more Smart Citation
“…They found T g between −15 • C and −38 • C, which is in agreement with values retrieved in Table 1. It is not straightforward to compare passive satellite measurements with models: Hoose et al (2018) showed that some processes such as rime splittering at −10 • C are not detectable by passive satellites due to spatial resolution coarser than 1 km. Also, the cloud top phase transition temperature is more likely to be shifted to higher temperatures than in cloud due to a stronger Wegner-Bergeron-Findeisen process at cloud top (Hoose et al, 2018;Korolev et al, 2017).…”
Section: Larger Cth Have Been Observed Associated With Larger Rmentioning
confidence: 99%
“…It is not straightforward to compare passive satellite measurements with models: Hoose et al (2018) showed that some processes such as rime splittering at −10 • C are not detectable by passive satellites due to spatial resolution coarser than 1 km. Also, the cloud top phase transition temperature is more likely to be shifted to higher temperatures than in cloud due to a stronger Wegner-Bergeron-Findeisen process at cloud top (Hoose et al, 2018;Korolev et al, 2017). Therefore, when comparing cloud top information from passive satellite with vertical distribution from active satellite, the temperature transition is more likely to be higher for passive satellites.…”
Section: Larger Cth Have Been Observed Associated With Larger Rmentioning
confidence: 99%
“…A binary cloud phase assumption for cloudy pixels is derived following earlier studies (Hoose et al 2018;Han et al 2023) to mimic satellite products of the cloud-top phase. A cloudy pixel having a liquid mass fraction larger than 0.5 is recognized as a liquid pixel.…”
Section: B Sensitivity Of Cloud Phase To Sipmentioning
confidence: 99%
“…Cloud phase distribution of mixed-phase clouds impacts cloud radiative properties, cloud dynamics, and cloud lifetime. A lot of works have focused on the partitioning between ice and liquid and the phase transition from liquid to ice in mixed-phase clouds using numerical simulations and remote sensing retrievals (McCoy et al 2016;Hoose et al 2018;Coopman et al 2020;Bruno et al 2021;Coopman et al 2021). Observations and simulations reveal that cloud phase distributions depend on not only temperature but also cloud type and SIP processes (Rosenfeld et al 2011;Hoose et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation